2018
DOI: 10.1209/0295-5075/123/15001
|View full text |Cite
|
Sign up to set email alerts
|

Complex plasma in glow discharge in a strong magnetic field

Abstract: Experimental investigation of the rotation of dust structures in a DC discharge in a longitudinal strong magnetic field up to B = 1 T has been performed for the first time. The main problem is the occurrence of discharge instability in moderate fields B > 0.1 T, which we have been able to solve. The dependence of rotation velocity on B is obtained. In fields B < 0.1 T the results are consistent with previous experiments, including rotation inversion. At B > 0.1 T (with the exception of the instability region),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…The ongoing magnetic field increase close to the diapason from 1.2 × 10 3 to 10 4 G results in a smaller growth of the angular velocity (the rate of change is 0.2 × 10 −3 rad/(s G)). According to the proposed analysis, this behaviour may be associated with the decrease in effect of the eddy electron current caused by significant deformation (lengthening) of the dust trap in a standing striation. In addition, we note that in the range from 3 × 10 3 to 4 × 10 3 G, which corresponds to current‐convective instability in a glow discharge, both the local rotation velocity decrease and the significant loss of the dust from structures are observed.…”
Section: Results and Qualitative Interpretationmentioning
confidence: 96%
See 2 more Smart Citations
“…The ongoing magnetic field increase close to the diapason from 1.2 × 10 3 to 10 4 G results in a smaller growth of the angular velocity (the rate of change is 0.2 × 10 −3 rad/(s G)). According to the proposed analysis, this behaviour may be associated with the decrease in effect of the eddy electron current caused by significant deformation (lengthening) of the dust trap in a standing striation. In addition, we note that in the range from 3 × 10 3 to 4 × 10 3 G, which corresponds to current‐convective instability in a glow discharge, both the local rotation velocity decrease and the significant loss of the dust from structures are observed.…”
Section: Results and Qualitative Interpretationmentioning
confidence: 96%
“…We must notice that Figure shows dynamics of the angular velocity of the structure's central horizontal section. Dzlieva et al qualitatively discussed the origins of these changes in structure rotation. Speaking of comparison with Figure , we can note the following.…”
Section: Results and Qualitative Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, where authors reported about instability of the dc discharge and its influence on dusty plasma, there was a number of works performed in the conditions of rf discharge in magnetic field up to 2 × 10 4 G . In recent work, it was succeeded to create the dusty plasma in the conditions of the stratified glow discharge in a whole diapason of moderate magnetic field in neon. In this work, we want to discuss some aspects of the impact of moderate and strong magnetic field on plasma of glow discharge in the presence of dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have identified several physical phenomena associated with the dusty structures, their geometry, their dynamics in a magnetic field, and the ordering of particles. Nowadays, studies of dusty plasmas in magnetic fields continue, and the magnetic field magnitude range has been sufficiently widened . And the higher range of magnetic induction is a subject of certain interest of current research.…”
Section: Introductionmentioning
confidence: 99%